UbiqStack: a taxonomy for a ubiquitous computing software stack - Modahl, Martin; Agarwalla, Bikash; Saponas, Scott; Abowd, Gregory; Ramachandran, Umakishore (Personal and Ubiquitous Computing, 2006)
This paper describes a taxonomy for a ubiquitous computing software stack called UbiqStack. Through the lens of the UbiqStack taxonomy we survey a variety of subsystems designed to be the building blocks from which sophisticated infrastructures for ubiquitous computing are assembled. Our experience shows that many of these building blocks fit neatly into one of the five UbiqStack categories, each containing functionally-equivalent components. Effectively identifying the best-fit ‘‘Lego pieces’’, which in turn determines the composite functionality of the resulting infrastructure, is critical. The selection process, however, is impeded by the lack of convention for labeling these classes of building blocks. The lack of clarity with respect to what ready-made subsystems are available within each class often results in naive re-implementation of ready-made components, monolithic and clumsy implementations, and implementations that impose nonstandard interfaces onto the applications above. This paper describes the UbiqStack classes of subsystems and explores each in light of the experience gained over 2 years of active development of both ubiquitous computing applications and software infrastructures for their deployment.